Structural modification on organic compounds containing α,β- conjugated keto-enol group and schiff base for the photophysical properties investigation - Tiong, Mee Hing (Universiti Malaysia Sarawak (UNIMAS), 2014)
This study consists of three parts, which are (i) the synthesis of bis-chalcone and their photophysical properties studies; (ii) the synthesis of α,β-conjugated Schiff base and spectroscopic characterization; (iii) the complexation reaction on both bis-chalcone and α,β-conjugated Schiff base. The result from fundamental photophysical measurements of bis-chalcone compounds showed that the λmax of emission shifted to lower energy after having the OCH3 group at the center phenyl ring. Bis-chalcone 2a showed solvatochromism behavior and the emission wavelength increased from 499 nm (benzene) to 523 nm (MeCN). The presence of electron donating or withdrawing group as substituent in α,β-conjugated Schiff base can give an electronic effect on C=N moiety. The electron donating group caused shielding effect to the proton at C=N group, which resulted in upfield proton, whereas, the electron withdrawing group, a downfield proton of C=N was observed. The C=O and C=N bonds in bis-chalcone and α,β-conjugated Schiff base respectively have significantly shifted either to a lower or higher frequency after forming a complex in their IR spectra. For both type of complexes, a π bonding from metal centre to the Cα=Cβ bond was observed in the IR and NMR spectra.